Immobilization of Cellulase Using Polysulfone Membrane - Wei, Ping; Qin Zhang, Hao; Zhen Wan, Ya; Dun Liu, Jin; Gang Zhang, Yong (Asian Journal of Chemistry, 2010)
Cellulase has been successfully immobilized in polysulfone by means of cross-linking and filtration with pressure The optimum conditions for the preparation of the immobilized enzyme and the characteristics of the immobilized enzyme were obtained. The cellulase exhibited improved stability in reaction conditions over a broad temperature range and an optimal pH value of 3.6 after being immobilized on the polysulphone membrane. The value of the Michaelis constant (Km) of the immobilized cellulase (26.853 g/L) was higher than that of the free one (11.577 g/L), whereas the maximum velocity (Vmax) was lower for the free one. Storage stability and temperature endurance of the immobilized cellulase were found to increase greatly and the immobilized cellulase retained 38.5 % of its initial activity after 6 successive batch reactions.